Comparative Study of Civil Legal Subjects of Actors of Tort Based on Legal Normal and Custom Aspects - Fujiansyah, Septian; Purba, Hasim; Barus, Utary Maharany; Kaban, Maria (KnE Social Sciences, 2024)
From a legal standpoint taking rights from other legal subjects might result within legal ramifications. One of the actions that can result in the imposition of legal consequences for subjects who violate these norms is when they commit an unlawful act (PMH). Chapter 1365 within the Civil Code provides the legal basis for tolerating PMH broadly in Indonesia. This form of study falls under normative judicial and uses supplementary information through analyzing information across all three layers of legal resources. Document study data collection techniques, using qualitative analysis. According to the study’s findings, it is known that the juridical position between legal norms and customs in viewing PMH is carried out by civil law subjects, from the point of view of legal norms guided by Art. 1352 and Art. 1353, then the elements are adjusted in accordance with the Civil Code’s Art. 1365, whereas its habitual stance refers to Art. 5 par. (1) Law Number 48 of 2009 and as Art. 18B par. (2) of the 1945 Constitution. Furthermore, the legal implications from the aspect of legal norms and customs for civil law subjects who carry out PMH, from the aspect of the norm, must fulfill the elements in Art. 1365 of the Civil Code, namely must violate the law, conflict with the rights of others, there are losses and mistakes, then compensation can be applied to the subject of the PMH perpetrator. The implementation with regulatory significance is determined by regional customary legal systems. Keywords: comparative, act against the law, norm, habit